O estágio como contributo da formação docente em Geografia: articulação entre escola e universidade - Albuquerque, Maria de Jesus Ferreira César de (2022)
This tesis talk about an experience in the degree course in Geography at a Federal University, in the municipality of Oiapoque, extreme north of Brazil. And it was because of the Supervised Internship discipline that the restlessness arose about the theme and the relationship it has with teacher training. The problem that guides the research is centered on the following research question: how the Supervised Internship, through its curricular systematization, contributed to the teacher training of graduates of the classes of the 2014.1, 2014.2 e 2015.1, of the Degree in Geography, Campus Oiapoque, UNIFAP. The main objective was to analyze the relevance of the curriculum in the plural and critical-reflexive formation of the graduates of the aforementioned classes, based on the analysis of the reports arising from the supervised internship experiences. Specifically, we are guided by the following objectives: a-) to find out how knowledge was constructed theoretical knowledge acquired during the academic training of graduates of the aforementioned classes and their articulation with the teaching practice developed in the Internship; b-) to analyze the curricular structure of the Geography course at Campus Oiapoque, from UNIFAP regarding the organization and systematization of workload and referrals of the Supervised Internship disciplines in order to observe the relationship and relevance to the legal bases that underlie the Internship and legitimize teacher training; c-) verify how the students understand/conceive the Supervised Internship from the exchange between the university and the school reality; d-) to verify the impacts of the Internship in the academic formation and what are the challenges that the teaching profession imposes to the graduates of the groups involved in this research. They served as a theoretical basis, above all, the postulates of Imbernón (1994); Bardin (2011); David Hamilton (1992; 1993); Cury, Reys and Zanardi (2018); Feldmann (2009); Feldmann and Masetto (2012), Sacristán (1999; 2013); Chizzotti and Casali (2012); Ponce (2016); Ponce and Rose (2014); Chizzotti and Ponce (2012), Martins (2010); Mészáros (2005), among others. The instruments used to collect data for writing the thesis were: analysis of official documents concerning education, Political Project of the Geography Degree Course of the institution, student reports delivered at the end of the Supervised Internship discipline. From the analysis of 25 reports, we proceeded with the content analysis technique, under the guidance of Bardin (2011). As a result, we came to the conclusion that the activities of the Supervised Internship were of significant relevance for the training of trainees in geography. However, for a more plural, critical-reflexive training that encompasses local specificities, reformulations of the PPC are urgently needed. allocating more hours to practical activities, which enhances the degree, as well as the UNIFAP Institution offering favorable and efficient conditions for Supervised Internship activities, how to establish partnerships with grantor schools located, for example, in indigenous villages and in peripheral areas of the municipality of Oiapoque, revealing, therefore, the Supervised Internship not only as a facilitating element of instruction, but as an instrument capable of promoting social transformation